Tribromomelamine: A Novel and Efficient Catalyst for the Synthesis 2-Arylthiazolines under Solvent-free Conditions - Liqiang Wu (E-Journal of Chemistry)
A novel procedure for the synthesis of 2-arylthiazolines through one-pot condensation of of nitriles with 2-aminoethanethiol in the presence of tribromomelamine as catalyst under solvent-free conditions is described.